Long lived liver-resident memory T cells of biased specificities for abundant sporozoite antigens drive malaria protection by radiation-attenuated sporozoite vaccination. - Maria N de Menezes; Zhengyu Ge; Anton Cozijnsen; Stephanie Gras; Patrick Bertolino; Irina Caminschi; Mireille H Lahoud; Katsuyuki Yui; Geoffrey I McFadden; Lynette Beattie; William R Heath; Daniel Fernandez-Ruiz (PLoS Pathogens)
Vaccination with radiation-attenuated sporozoites (RAS) can provide highly effective protection against malaria in both humans and mice. To extend understanding of malaria immunity and inform the development of future vaccines, we studied the protective response elicited by this vaccine in C57BL/6 mice. We reveal that successive doses of Plasmodium berghei RAS favour the generation of liver CD8+ tissue-resident memory T cells (TRM cells) over circulating memory cells and markedly enhance their longevity. Importantly, RAS immunisation strongly skews the composition of the liver CD8+ TRM compartment towards cells specific for abundant sporozoite antigens, such as thrombospondin-related anonymous protein (TRAP) and circumsporozoite protein (CSP), which become major mediators of protection. The increased prevalence of sporozoite specificities is associated with limited intrahepatic attenuated parasite development and inhibition of naïve T cell responses to all parasite antigens, whether formerly encountered or not, in previously vaccinated mice. This leads to the exclusive expansion of effector T cells formed upon initial immunisation, ultimately reducing the diversity of the liver TRM pool later established. However, stronger responses to less abundant epitopes can be achieved with higher initial doses of RAS. These findings provide novel insights into the mechanisms governing malaria immunity induced by attenuated sporozoite vaccination and highlight the susceptibility of this vaccine to limitations imposed by strain-specific immunity associated with the abundant, yet highly variable sporozoite antigens CSP and TRAP.